The Effect of Four Square Writing Method (FSWM) through Picture Series in Writing Narrative Text for Eleventh Grade at SMA Nusantara Balongpanggang - Rofi’ah, Anisatur; Ma’rifah, Ulfatul (Jetlal, 2017)
Good writing is important aspect in teaching writing subject. But the students find some problems that they faced in their writing which is in generating and organizing the ideas. Besides, the teacher also has problems in applying the appropriate method and media in teaching writing. Based on the previous studies, four square writing method gave the positive effect for the students. This study was to examine the significant effect of four square writing method through Picture Series in Writing Narrative Text for Eleventh Grade at SMA Nusantara Balongpanggang. And the researcher uses quasi experimental design. The researcher chose eleventh grade at SMA Nusantara Balongpanggang which totally consisted of 31 students. The researcher used cluster sampling because the school has been determined the classification of the students. It was included 16 students of XI-IPA as the experimental group and 15 students of XI- IPS as the control group. The data was collected by using tests; pre-test and post- test about writing narrative text. After getting the data, the researcher analyzed the data using SPSS 16.0 and used Independent Sample T test. The research finding showed that there was a significant difference between experimental group that were taught by using four square writing method andcontrol group that were taught by think pair share. It was proven by the result of sig. (2-tailed) is .000. The sig. (2-tailed) is lower than 0.05 (0.00 < 0.05) so, null hypothesis (Ho) can be rejected. The researcher concluded that four square writing method gave positive effect on students’ writing skill. The students were motivated and independent in learningwriting especially in generating and organizing the ideas. Therefore, the researcher suggests to the English teacher forimplementing of four square writing method through Picture Series as an alternative method in English teaching learningprocess and hopes to use four square writing method in other skills and levels to make different with the previous study.